(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Human Toxocariasis, caused by Toxocara spp. larvae, is a fecal-oral zoonotic disease. The infection typically presents as asymptomatic seropositivity or severe syndromes like Visceral Larva Migrans (VLM). The high prevalence in Vietnam and behavioral factors (such as pet ownership and poor hygiene) pose a significant public health concern, driving this study in Ba Ria – Vung Tau province. Objectives: (i) To determine the seroprevalence of Toxocara spp.. (ii) To describe the factors associated with Toxocara spp. seropositivity. Methods: A cross-sectional descriptive study was conducted on 506 patients examined at Ba Ria Hospital. Data were collected through KAP (Knowledge, Attitudes, Practices) interviews and an ELISA assay for the diagnosis of IgG antibody against Toxocara spp., along with Eosinophil count (Eos). Statistical analysis employed logistic regression to determine the Odds Ratio (OR) for independent risk factors. Results: 1. The overall seroprevalence was 16.0% (81/506). 2. Four statistically significant independent risk factors were identified: Failure to deworm pets (OR = 3.08; p < 0.001) was the strongest risk factor; Eosinophilia (elevated Eosinophil count) (OR = 2.45; p < 0.001); Agriculture and Small Business occupation (OR = 1.96; p = 0.004); and frequent consumption of raw vegetables (OR = 1.52; p = 0.019). Conclusion: The exposure rate to Toxocara spp. at the study site was 16.0%. Behavioral and environmental risk factors (especially poor pet management) played a dominant role. Education campaigns focusing on routine pet deworming and food hygiene must be strengthened to control infection.